Analysis of The Implementation of PSAK 101 in The Financial Statements of Bank BSI Medan City - Badriah Daulay; Rizka Dwi Ramadhani; Susi Susi; Grace Sitompul; Meigia Nidya Sari (CV. AFDIFAL MAJU BERKAH, 2025)
This study is intended to determine the implementation of PSAK 101 in the presentation and preparation of financial statements at Bank BSI in Medan.PSAK 101 is a statement of financial accounting standards that regulates the basis for the presentation of financial statement records for sharia entities. This statement regulates the presentation requirements, structure and minimum requirements for the content of financial statements. The research method used is qualitative descriptive with a case study approach, where data is collected through document analysis, literature study of BSI's financial statements. The results of the study show that Bank BSI Medan City has implemented most of the provisions in PSAK 101, including the presentation of financial position statements, comprehensive income statements, cash flow statements, and equity change reports in accordance with sharia principles.